Purification and analysis of lactate dehydrogenase from Plasmodium vivax - Aslan, A.; Celik, V.; Turgut-Balik, D. (Blackwell Publishing, 2006)
[Abstract Not Available]
31st Congress of the Federation-of-European-Biochemical-Societies (FEBS) -- JUN 24-29, 2006 -- Istanbul, TURKEY